Necessity of Linkage of TEVT with Industry in Nepal - Bagale, Shiba (International Journal of Social Sciences and Management, 2018)
This paper highlights on the necessity of the coordination of the TVET institutions and the industry in Nepal. The main goal of TVET is to develop skillful human resource needed for the country which could generate employment opportunities and entrepreneurship. Similarly, industry is the place for the job market and performing the skills that is achieved. In the context of Nepal, different studies show that the TVET graduates are unemployed, employed but in low wage, employed but not fulfilling the industry need. This is because of lack of meeting the demand of the market need by TVET courses. If the linkage is done, it increases productivity and nations economy. But the most challenging part is meeting the industry goals and skills by academic courses of TVET. So, academic skills and industry skills needs to be matched by revisiting the curriculum and other strategies. Also the industrial human resource could be upgraded by providing occupational skills upgrading training. The labor market, need assessment of the human resource, identification of the industrial skills needs to be identified to make a strong linkage. Thus, this study suggests that the urgent need of the collaboration of the industry and the TVET for the overall and sustainable development of the country. Int. J. Soc. Sc. Manage. Vol. 5, Issue-4: 237-242